THE MANAGEMENT OF CREATIVE INDUSTRY IN STUDIO EDHI SUNARSO YOGYAKARTA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The main target of the research is to get data from the industrial management of Edhi Sunarso creative art that is located at Yogyakarta, because his creative industrial achievement is very phenomenal to  the world class and legendarist. The research method used are  etnografi and the research analysis is descriptive qualitative. Data gathering techniques used data reduction procedure through interview, observation and documentation. Data  analysis flew through data reduction procedure, presenting data and drawing conclusion. The research result of Edhi Sunarso’ creative art industrial  proved reach up the top of glory through inovative management, starting from the  management concept of painting, statue, technology and history. The Product of his crteative industrial mainly the beauty quality, functional and market’need. Edhi Sunarso’ projects has characteristic of big monumental, artistic, exspressive and heroic. His workings were mounted at many big cities or  even at the world, he got many awards that came from his own country and oversea. The highest award came from President, Governor, Art community and civitas academica such as: Empu Ageng award from ISI Yogyakarta.